Political Education as a Mandatory Law - Roman Hadi Saputro (Institut Pendidikan Indonesia, 2021)
The aim of the research entitled Political Education as a Mandate of Law is to find out what and how political education is and how political education is delivered to the public in accordance with the mandate of Law No. 2 of 2011 concerning Political Parties. Several political parties in Indonesia already have plans to provide political education to the public by holding party schools or seminars with the theme of political education. However, in its implementation, there were problems that hampered the program that had been designed and established. The obstacle often faced by political parties in providing political education to the public is that people are often skeptical of political parties due to various problems that exist within the political party itself. Starting from internal problems such as dualism in leadership to external problems such as being caught in corruption cases, it becomes a problem for political parties in providing political education. In dealing with this problem, the role of all elements of the political party, from the chairman to the sympathizers, is needed to restore the image of the political party so that it can provide political education to the public.